2013
DOI: 10.1024/1010-0652/a000110
|View full text |Cite
|
Sign up to set email alerts
|

Effekte eines Trainings der phonologischen Bewusstheit bei Vorschulkindern mit unterschiedlichem Sprachhintergrund*

Abstract: Die phonologische Bewusstheit gilt als bedeutsamer Prädiktor des Erfolgs beim Lesen- und Schreibenlernen. Allerdings existieren nur wenige empirische Studien zur Trainingseffektivität von Programmen zur Förderung der phonologischen Bewusstheit bei Kindern mit unterschiedlichem Sprachhintergrund. Das Ziel der vorliegenden Studie liegt daher in der Untersuchung von Effekten eines Trainingsprogramms zur vorschulischen Förderung der phonologischen Bewusstheit und der Buchstaben-Laut-Verbindungen bei Kindern mit un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…In line with earlier research (Schneider et al, 1997; Schöppe et al, 2013), we found that the training is effective in promoting phonological awareness (narrow). The regression analyses provide further evidence that this also applies to the phonological awareness (broad) for the group with weak initial phonological awareness skills.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with earlier research (Schneider et al, 1997; Schöppe et al, 2013), we found that the training is effective in promoting phonological awareness (narrow). The regression analyses provide further evidence that this also applies to the phonological awareness (broad) for the group with weak initial phonological awareness skills.…”
Section: Discussionsupporting
confidence: 92%
“…However, despite showing similar gains in phonological awareness overall, the minority language children continued to lag behind their majority-language peers in the level of phonological awareness they reached after the intervention. The training could thus not fully compensate the initial disparities (see also Schöppe et al, 2013 for similar results).…”
Section: Introductionmentioning
confidence: 86%
“…In contrast to other tests using pseudowords (e.g., Hasselhorn et al, 2012), the items were based on quasi-universal structures, with common vowels and consonants, a simple syllable structure (without language-specific structures like consonant clusters) and without morphology (see task description in section “Materials”). We consider this approach essential to assess actual phoneme-based spelling performance in groups with diverse language experience and proficiency (Schöppe et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of 43 studies using phonemic awareness tests, a small but significant effect was found in favor of the first-language learners (Melby-Lervåg and Lervåg 2014). For L2 learners of German, some studies reported phonological awareness performance comparable to native German children (Czapka et al 2019;Duzy et al 2013a, b;Limbird et al 2014;Limbird and Stanat 2006), whereas others found group differences in favor of the native children (Blatter et al 2013;Pröscholdt et al 2013;Schöppe et al 2013;Weber et al 2007). Like in native-speaking children, phonological awareness predicts reading and spelling skills in L2 learners of English (Harrison et al 2016;Jongejan et al 2007;Quiroga et al 2002) and German (Czapka et al 2019;Duzy et al 2013a;Limbird et al 2014).…”
Section: Training Components and Their Role In L1 And L2 Literacy Acqmentioning
confidence: 99%
“…Like in native-speaking children, phonological awareness predicts reading and spelling skills in L2 learners of English (Harrison et al 2016;Jongejan et al 2007;Quiroga et al 2002) and German (Czapka et al 2019;Duzy et al 2013a;Limbird et al 2014). Furthermore, phonological awareness training fosters early literacy skills in L2 (Blatter et al 2013;Schöppe et al 2013;Weber et al 2007;Yeung et al 2013).…”
Section: Training Components and Their Role In L1 And L2 Literacy Acqmentioning
confidence: 99%